Remission of relapsed/refractory classical Hodgkin lymphoma induced by brentuximab vedotin and pembrolizumab combination after allogeneic hematopoietic stem cell transplantation: a case report - Giannotti, Federica; De Ramon Ortiz, Carmen; Simonetta, Federico; Morin, Sarah; Bernardi, Chiara; Masouridi-Levrat, Stavroula; Chalandon, Yves; Mamez, Anne-Claire (Frontiers in Immunology, 2024)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a potentially curative treatment option for patients with highly chemorefractory Hodgkin lymphoma (HL). The CD30-targeting antibody-drug conjugate Brentuximab-Vedotin (BV) and programmed cell death protein-1 (PD-1) blocking agents have demonstrated clinical activity with durable responses in relapsed/refractory (r/r) HL. However, patients with a history of allo-HSCT were frequently excluded from clinical trials due to concerns about the risk of graft-versus-host disease (GVHD). We report the clinical history of a patient with refractory classical HL who underwent two allo-HSCTs (first from matched unrelated and second from haploidentical donor) after relapsing on BV and nivolumab and for whom durable remission was finally obtained using BV-pembrolizumab combination for relapse after haploidentical HSCT. Such treatment was associated with the onset of GVHD after only two cycles which led to treatment discontinuation. However, the side effects were rapidly controlled, and after 2 years of follow-up, the patient is still in remission. Our data support the feasibility and efficacy of combining PD-1 blockade with BV to enhance the graft-versus-lymphoma effect after allo-HSCT.